Developing a CHARGE syndrome checklist: Health supervision across the lifespan (from head to toe). Issue 3 (4th February 2017) - Trider, Carrie‐Lee; Arra‐Robar, Angela; van Ravenswaaij‐Arts, Conny; Blake, Kim
Abstract : Health supervision and management considerations for individuals with CHARGE syndrome are often complex, and a comprehensive approach is essential. The Atlantic Canadian CHARGE syndrome team developed a checklist organized by body system and age to aid healthcare providers in their approach to the ongoing care of these individuals. The checklist was evaluated qualitatively using a modified Delphi method with widespread consultation from expert healthcare practitioners, parents, and individuals with CHARGE syndrome. These are the first comprehensive guidelines across the lifespan of CHARGE syndrome that suggest a consistent approach to medical surveillance, investigations, and management for the physician and the multi‐disciplinary team caring for these individuals. We anticipate that these guidelines will provide improvements in care by preventing missed diagnoses, allowing for anticipatory counseling, and facilitating early referral for interventions and treatments. © 2017 Wiley Periodicals, Inc.